2018
DOI: 10.4172/2150-3508.1000250
|View full text |Cite
|
Sign up to set email alerts
|

Has the Latest Fish Introduction in Lake Naivasha Improved Income of Fishermen? The Economics of Nile Tilapia (Oreochromis niloticus) in Lake Naivasha

Abstract: Data used in this study was collected daily between January 2011 and April 2016 from four fish landing beaches along the shores of Lake Naivasha; Central, Karagita, Kamere and Tarambete beaches. The results revealed that the total landings of Nile tilapia Oreochromis niloticus has been gradually increasing from a 0% in 2011 to 42.7% (206.923 tons) of the total landings between January and April 2016 (422.613 tons) with projections of it surpassing carp by December 2016. These findings corroborate regular field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The dominance of carp was observed until 2015 (Ojuok et al, 2007;Yongo et al, 2021), whereby carp catches were estimated at 83.4% of the total fish catch, followed by C. gariepinus (19%), O. niloticus (7.3%) and O. leucostictus (6.0%) (Njiru et al, 2017;Waithaka et al, 2018). As previously mentioned, O. niloticus was re-introduced into the lake in 2011, after which Keyombe et al (2018) reported O. niloticus landings have been gradually increasing from 0% in 2011 to 42.7% (206.923 tons) in 2016 (Figure 9). Finally, the recent catch assessment survey in Lake Naivasha revealed the lake fishery has shifted, with the catches are presently dominated by O. niloticus (68.9%), followed by carp (29.1%), with other species contributing to less than 1% of the total catch (Table 5; Waithaka et al, 2018).…”
Section: Zooplankton and Benthic Invertebratesmentioning
confidence: 81%
See 1 more Smart Citation
“…The dominance of carp was observed until 2015 (Ojuok et al, 2007;Yongo et al, 2021), whereby carp catches were estimated at 83.4% of the total fish catch, followed by C. gariepinus (19%), O. niloticus (7.3%) and O. leucostictus (6.0%) (Njiru et al, 2017;Waithaka et al, 2018). As previously mentioned, O. niloticus was re-introduced into the lake in 2011, after which Keyombe et al (2018) reported O. niloticus landings have been gradually increasing from 0% in 2011 to 42.7% (206.923 tons) in 2016 (Figure 9). Finally, the recent catch assessment survey in Lake Naivasha revealed the lake fishery has shifted, with the catches are presently dominated by O. niloticus (68.9%), followed by carp (29.1%), with other species contributing to less than 1% of the total catch (Table 5; Waithaka et al, 2018).…”
Section: Zooplankton and Benthic Invertebratesmentioning
confidence: 81%
“…The growth in human population also has resulted in increased domestic effluent pollutant discharges into the lake. Fertilizers, pesticides and effluent produced by the Naivasha floricultural industry are the other diffuse F I G U R E 9 Annual total landings and value of Nile tilapia (Oreochromis niloticus) from Lake Naivasha (data adapted fromKeyombe et al, 2018) TA B L E 5 Daily composition of fish catches in Lake Naivasha, Kenya(Waithaka et al, 2018)…”
mentioning
confidence: 99%
“…Dissolved oxygen levels were higher during the rainy season (Olagbemide and Owolabi 2019), and thus, the water became well-saturated with oxygen, leading to the effective functioning of the fish's metabolic processes. Shinkafi and Ipimiolu (2010), Ibrahim et al (2011), Keyombe et al (2017), and Mohd and Khaironizam (2019) reported similar higher value of condition factors during the rainy season than the dry season.…”
Section: Condition Factormentioning
confidence: 89%
“…accumulation of fat and gonads development) [42,58] and stage of maturity [59,60]. Improved and better environmental conditions (physicochemical and biological parameters) are associated to higher the condition factor of fishes and vice versa [42,61,62]. This agrees strongly with the results in the present study whereby the higher condition factor and growth performance of uninfected fishes as well as fishes sampled during the dry season when most of the water quality parameters were within the satisfactory ranges.…”
Section: Discussionmentioning
confidence: 99%